First Sprayable Double-Stranded RNA-Based Biopesticide Product Targets Proteasome Subunit Beta Type-5 in Colorado Potato Beetle (Leptinotarsa decemlineata) - Rodrigues, Thais B.; Mishra, Sambit K.; Sridharan, Krishnakumar; Barnes, Ethann R.; Alyokhin, Andrei; Tuttle, Rich; Kokulapalan, Wimalanathan; Garby, David; Skizim, Nicholas J.; Tang, Yu-wen; Manley, Brian; Aulisa, Lorenzo; et al. (Frontiers in Plant Science, 2021)
Colorado potato beetle (CPB, Leptinotarsa decemlineata) is a major pest of potato and other solanaceous vegetables in the Northern Hemisphere. The insect feeds on leaves and can completely defoliate crops. Because of the repeated use of single insecticide classes without rotating active ingredients, many chemicals are no longer effective in controlling CPB. Ledprona is a sprayable double-stranded RNA biopesticide with a new mode of action that triggers the RNA interference pathway. Laboratory assays with second instar larvae fed Ledprona showed a dose–response where 25×10−6g/L of dsPSMB5 caused 90% mortality after 6days of initial exposure. We also showed that exposure to Ledprona for 6h caused larval mortality and decreased target messenger RNA (mRNA) expression. Decrease in PSMB5 protein levels was observed after 48h of larval exposure to Ledprona. Both PSMB5 mRNA and protein levels did not recover over time. Ledprona efficacy was demonstrated in a whole plant greenhouse trial and performed similarly to spinosad. Ledprona, currently pending registration at EPA, represents a new biopesticide class integrated pest management and insecticide resistance management programs directed against CPB.